Efektivitas Metode Pengolahan Limbah Cair Praktikum Indikator Alami Asam Basa - Abdul Manan; Sulasfiana Alfi Raida; Arsyada Khilmiyati; Octavio Prayoga (Universitas Bojonegoro, 2026)
Laboratory waste is hazardous and toxic waste (B3) that has the potential to pollute the environment if not properly treated. This study aims to analyze the effectiveness of various sequences of physical, chemical, and biological methods in treating liquid waste from acid-base indicator experiments based on changes in color, pH, turbidity, and the condition of water hyacinth plants. The study employed a descriptive quantitative approach through a simple experiment consisting of four namely control (P0), filtration–neutralization–phytoremediation (P1), neutralization–filtration–phytoremediation (P2), and sedimentation–precipitation–phytoremediation (P3). Observations of color, pH, turbidity, and the condition of water hyacinth plants were conduced for seven consecutive days. The results showed that treatment P2 had the highest effectiveness at 86%, followed by P1 at 71%, and P3 at 29%. Treatment P2 produced wastewater with a clearer color, neutral pH, low turbidity, and was able to maintain plant condition until the end of the observation period. Thus, the neutralization–filtration–phytoremediation sequence is the most effective method for improving the quality of wastewater from natural acid-base indicator laboratory experiments.